Filsafat Analitik: Kajian Tokoh dan Pemikirannya (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
The discussion of Analytic Philosophy that is often raised is very close to the philosophy of language. There are those who equate the study of analytic philosophy with a language philosophy. Analytical philosophy does pay attention to the use of language and the meaning conveyed. Of course, the characteristic of analytic philosophy which prioritizes links with language analysis should reveal the diversity of analytic philosophies. In this article, we will examine 4 philosophers who are in analytic philosophy, namely Edmund Husserl, Rudolf Carnap, Rudolf Quine, and Hillary Putnam. This research resulted in studies namely (1) philosophical studies showing the existence of logical analysis in a scientific concept and statement; (2) The thought used, the language used by humans must be tested as language as long as the thought is conveyed with or through language that allows it to achieve universal or logical power in the order of science or the language of science; (3) regarding all metaphysics based on non-empirical existence or perhaps belief in internal relations that are external. The observable world of plurality with external relations or is a logical entity.
Keywords: Philosophy; analytic studies; figures; thoughts